Corredor Bioceânico: Efeitos e Perspectivas sobre os Direitos Humanos Sociais - JOÃO VICTOR MACIEL DE ALMEIDA AQUINO (2023)
The Bioceanic Corridor is a unique developmental project that covers the construction of a road path, which integrates infrastructures of Brazil, Paraguay, Argentina and Chile, with the objective of facilitating the transit and trade of goods, with regional and international markets, highlighting among these the Asian, where the largest consumer markets of products in the region are found. In addition to this economic issue, the Corridor will be able to provide opportunities for endogenous development and favoring exploration and expansion of other economic activities throughout their length and breadth on the American continent. Thus, the Corridor is strategic for the economic development of the state of Mato Grosso do Sul, Brazil and the other countries covered by it, mainly because of its geographical position and socioeconomic dynamics. It happens, however, because it is an projecto whose central objective is economic, the effects and externalities of the project have not yet been directly addressed, adding situations that already occur and others that are visualized, with emphasis on human and social aspects. It is seen that, due to the close relationship with economic development, work will be the central axis of part of these effects. which causes an allocation in the rights directly and indirectly related to labor, which function as minimum parameters and tools for protection. Social human rights are relevant in this sense, which in content encompass several of these situations, with genesis in the work, that are already developing and that with the effective implementation of the Corridor will have more space. Thus, the objective of this research is to evaluate how the Bioceanic Corridor is able to impact social human rights in the face of the use/expansion of labor exploitation in the region. In addition, how social human rights can serve as parameters, in their different facets, for the protection of labor, social security and other human rights in the face of a project whose central objective is eminently economic? It is verified as a hypothesis the occurrence of problems related to social rights throughout the context of the Corridor, with greater or lesser intensity depending on the location, arising from the structuring of the project and the transformations that it imports. There is a need to think about the existing structures for the protection of these rights and articulation of elements such as transnationality and the multiplicity of legal systems and norms applicable to these social relations. To this end, it made use of the hypothetical-deductive method, with the analysis and comparison of diverse bibliographic material.